2021
DOI: 10.1002/agj2.20500
|View full text |Cite
|
Sign up to set email alerts
|

Target‐site resistance and cross‐resistance to ALS‐inhibiting herbicides in radish and wild radish biotypes from Brazil

Abstract: Radish (Raphanus sativus L.) and wild radish (R. raphanistrum L.) are troublesome agricultural weeds in several areas worldwide, with populations resistant to acetolactate synthase (ALS) inhibitor herbicide. Information on the mechanisms of resistance is important for management and developing novel solutions to control resistant populations. The objective of this work was to determine the ALS‐resistance mechanisms in radish and wild radish biotypes resistant to ALS‐inhibiting herbicides. Resistance levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
11
0
2
Order By: Relevance
“…A 630 bp region of ALS gene was sequenced that contained Trp‐574‐Leu mutation which has been reported to confer resistance to metsulfuron in resistant biotypes (da Costa et al., 2021). Phylogenetic analysis (depicted in Figure 3) revealed that ALS gene in toothed dock biotypes is highly similar to wild buckwheat (Beckie et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A 630 bp region of ALS gene was sequenced that contained Trp‐574‐Leu mutation which has been reported to confer resistance to metsulfuron in resistant biotypes (da Costa et al., 2021). Phylogenetic analysis (depicted in Figure 3) revealed that ALS gene in toothed dock biotypes is highly similar to wild buckwheat (Beckie et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In South America, feral radish developed resistant to AHAS-inhibitors in Chile, Brazil and Argentina which is due to the Trp574Leu mutation (Pandolfo et al, 2016; Costa et al, 2021; Heap, 2022), that showed considerable fitness cost in both agrestal and ruderal environments under field conditions (Vercellino et al, 2018, 2021a). Considering that the radish cover crop is susceptible to AHAS-inhibitors, it could be cultivated in areas infested with AHAS-resistant feral radish to flood their populations with the AHAS-susceptible allele and contribute to reducing the frequency of the AHAS-resistant allele.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivated radish is an ancient crop domesticated independently in both Europe and South Asia (Zhang et al, 2021) and selected for multiple purposes, including human consumption as roots (botanically hypocotyl plus root), forage and cover crops (Snow and Campbell, 2005). R. sativus is not known in the wild (Warwick, 2011); however, feral populations of radish have been found as a weed infesting crops in several parts of the world, including North America, South America and South Africa (Hegde et al, 2006; Barnaud et al, 2013; Vercellino et al, 2018; Costa et al, 2021; Heap, 2022). In North America, its invasive capacity is attributed to the introgression with a closely related species R. raphanistrum (known as California wild radish) (Hegde et al, 2006; Ellstrand et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Weeds are one of the major biotic stress factors that significantly affect agricultural production and threaten food security around the world (Costa et al 2021), with an estimated cost of over US$30 billion yr −1 (Gould et al 2018). Favorable characteristics such as high stress tolerance and genetic variability enable weeds to adapt to various environments and survive in different cropping systems (Costa et al 2021). Ludwigia prostrata is an annual dicotyledonous weed of the Onagraceae family, widely distributed in rice fields in the south of China.…”
Section: Introductionmentioning
confidence: 99%